MATEMATIK ANALIZNING BA’ZI MASALALARINI YEChIShDA MAPLE DASTURIDAN FOYDALANISh USULLARI - Boboyarova, N.A.; Sobirov, U.M.; O‘rinboyeva, Z.O.; Abdullayev, J.Sh. (SCIENCE and SOCIETY, 2025)
This article explores how to solve some problems of the discipline "Mathematical Analysis", which is taught in mathematics courses in higher education institutions, using the Maple application software.
Keywords: Maple programm; limit of a function; derivative of a function; continuity of a function